Pengelolaan Limbah Medis Padat di Puskesmas Kota Pekanbaru - Anggi Pramana; Ivo Sartika; Titin Salim; Ruriz Akbar Primadona Harapan; Yoza Febriadi (Jurnal Zona, 2024)
This study aims to analyze the current state of solid medical waste management in Community Health Centers in Pekanbaru City from ecological, economic, and social perspectives, and to design a solid medical waste management model based on the SI MOLI (Waste Monitoring Application) concept. A mixed-method approach was employed, involving a sample of all 21 Community Health Centers (Puskesmas) in Pekanbaru City. The findings indicate that most of these centers have sufficient human resources and all have policies or Standard Operating Procedures (SOPs) in place for managing solid medical waste. However, while the centers have implemented waste sorting, their infrastructure remains inadequate, and temporary waste storage facilities are still not fully compliant with safety standards. Despite these challenges, part of the Community Health Centers' environmental health programs have successfully managed solid medical waste. The results of the bivariate analysis show a significant relationship (p-value less than 0.05) between human resources, policies/SOPs, infrastructure, waste sorting, temporary storage, and the overall waste management effectiveness in these centers. The proposed solid medical waste management model for Pekanbaru’s Community Health Centers incorporates the SI MOLI system. Given that nearly all centers generate more waste than their storage capacities can handle, the SI MOLI application is a timely and essential tool. This study recommends SI MOLI as a synthesis of empirical findings and existing theories and concepts from previous research to enhance waste management practices.